EPSILON TOXIN EPITOPES FROM CLOSTRIDIUM PERFRINGENS WITH REDUCED TOXICITY - TITBALL, RICHARD W; NAYLOR, CLAIRE; BOKORI-BROWN, MONIKA (2013)
There is provided an epsilon toxin epitope polypeptide comprising a sequence of at least 10 contiguous amino acids from SEQ ID NO:3, the sequence comprising a mutation of at least one tyrosine residue compared to the equivalent sequence in SEQ ID NO:3, the polypeptide being capable of binding an antibody which binds to SEQ ID NO:5 and having reduced toxicity compared with the toxicity of SEQ ID NO:5. The polypeptide is useful in a method of vaccinating a subject against developing a disease caused by Clostridium perfringens and/or caused by (or associated with the presence of) active epsilon toxin. L'invention concerne un polypeptide épitope de toxine epsilon comprenant une séquence d'au moins 10 acides aminés contigus provenant de SEQ ID NO:3, la séquence comprenant une mutation d'au moins un résidu tyrosine en comparaison à la séquence équivalente dans SEQ ID NO:3, le polypeptide étant apte à se lier à un anticorps qui se lie à SEQ ID NO:5 et ayant une toxicité réduite en comparaison à la toxicité de SEQ ID NO:5. Le polypeptide est utile dans une méthode de vaccination d'un sujet contre le développement d'une maladie provoquée par Clostridium perfringens et/ou provoquée par (ou associée à la présence de) la toxine epsilon active.